«Living in Paradise»: Contending Scenarios Among the Second Generation of Yucatecan Migrants in Cancun, Quintana Roo - Be Ramírez, Pedro Antonio (Revista Española de Antropología Americana, 2019)
This article looks to understand second-generation yucatecan migrants living in Cancun, Quintana Roo, Mexico that, within the context of local and global dynamics, identifies themselves as Mayans. Distinctive cultural forms and contents discussed here include their use of Native names and language, dress, in addition to other practices and customs that represent elements within shifting cultural politics that either differentiate or support Mayan identity. These Indigenous social and cultural references are transmitted from generation to generation, constituting an analytical backdrop where prestige and/or discrimination serve to underline the acceptance or rejection of Mayan cultural heritage.
Keywords: Yucatecan migrants; second generations; social and cultural practices; Yucatec Mayan culture; discrimination; prejudices